Implementación del programa de inspecciones planeadas en una planta de conversión de papel - González Villalba, María Verónica (2010)
The need to create and implement a program to help to identify hazards that result in the prevention of human and material losses and additional give support to the different management systems within an organization is that leads to the development of this project. The objective of this study is to propose a methodology for the implementation of a planned inspection program as a guide for any company that is seeking improvements in their management systems, a concern now shared by many organizations. This project is developed in a paper conversion plant but is easily adapted to different companies, based only on the guidelines referred to throughout this document